2018
DOI: 10.1016/j.jvs.2018.03.138
|View full text |Cite
|
Sign up to set email alerts
|

IP101. Identification of Predictors of High-Grade Restenosis After Carotid Endarterectomy in a Multicenter National Database

Abstract: Objective: Optimal anesthesia for carotid endarterectomy remains controversial. We evaluated and compared short-term outcomes after carotid endarterectomy with general anesthesia (GA) or regional anesthesia (RA).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It has been reported that severe carotid stenosis can cause cognitive dysfunction, and its mechanisms include chronic hypoperfusion, leukoaraiosis of the brain, and the central nervous system function decline caused by chronic ischemia and hypoxia [ 1 – 3 ]. Since the decline in cerebral perfusion can cause cognitive dysfunction, however, CAS and CEA can relieve blood vessel stenosis and significantly improve cerebral blood flow perfusion [ 4 – 7 ]. So, can both improve cognitive dysfunction caused by stenosis?…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that severe carotid stenosis can cause cognitive dysfunction, and its mechanisms include chronic hypoperfusion, leukoaraiosis of the brain, and the central nervous system function decline caused by chronic ischemia and hypoxia [ 1 – 3 ]. Since the decline in cerebral perfusion can cause cognitive dysfunction, however, CAS and CEA can relieve blood vessel stenosis and significantly improve cerebral blood flow perfusion [ 4 – 7 ]. So, can both improve cognitive dysfunction caused by stenosis?…”
Section: Introductionmentioning
confidence: 99%